Horrible Harry and the dungeon - Kline, Suzy.; Remkiewicz, Frank (New York : Scholastics, 1998)
It's almost summer vacation and the students in room 2B are having trouble concentrating on their butterfly project, until a frightening-looking new teacher comes to supervise the Suspension Room and Harry is sent there as punishment for unruly behavior.
G2
Keywords: Schools -- Fiction; Teachers -- Fiction; Butterflies -- Fiction